50 Synthesis, characterization and stability of five tavaborole-based pharmaceutical cocrystals. (19th December 2016) - Zhang, Xiaoming; Song, Jialong; Xie, Peng; Guo, Xiufen; Meng, Fanxin
Abstract : Objectives: Pharmaceutical cocrystals have received attention in the pharmaceutical industry due to their potential for readily changing the physicochemical and biological properties of free active pharmaceutical ingredients (API). Tavaborole is an antifungal agent with strong moisture absorption leading to poor stability. The objective of this investigation was to prepare five pharmaceutical tavaborole cocrystals and to optimize their stability. Methods: The five novel pharmaceutical cocrystals with tavaborole as the API were synthesised using the grinding method, with p-aminobenzoic acid (cocrystal 1), m-aminobenzoic acid (cocrystal 2), 2, 3'-dihydroxybenzoic acid (cocrystal 3), salicylic acid (cocrystal 4) and 2, 6'-pyridinedicarboxylic acid (cocrystal 5). Characterization with XRD and TGA further identified a new phase. The thermal stability, chemical stability and moisture absorption rate of API and cocrystals were also measured and discussed. Results: The thermal stability of the five cocrystals was significantly improved compared to the API alone. Chemical degradation and a hydration reaction of cocrystals did not occur in 43%, 58%, 75% and 92% relative humidity at 25°C. The moisture absorption rate of API and cocrystals decreased in the order: API>cocrystal 2>cocrystal 1>cocrystal 4>cocrystal 3>cocrystal 5. Conclusions: In this study, we used the grinding method to synthesize pharmaceutical cocrystals of tavaborole. The thermal stability, chemical stability and hygroscopic stability of cocrystals were significantly better than those of API alone. Acknowledgments: We are grateful to the Major International (Regional) Joint Research Project of NSFC (Grant No. 21120102034).